The rebirth of bourbon : building a tourism economy in small-town, USA - Coomes, Steve; Huston, Kim; Mangeot, Michael (Emerald Publishing Limited, 2020)
Welcome to Bardstown, KY: The Bourbon Capital of the World® Bourbon's popularity is now a global phenomenon, but you need only look at Bardstown, Kentucky, to see its remarkable and evolving impacts. This historic city of 13,500 people is booming as a result, but it's also enduring growing pains. The economic impacts from a massive influx of tourists to what is now America's bourbon epicenter are positive on many levels, but with those crowds comes pressure on infrastructure, services and accommodations. The demand for hotels, bars and restaurants is at an all-time high, and investors from across the globe are addressing those needs. Still, as a twocenturyold Kentucky cultural and entertainment center long before it was discovered by bourbon drinkers many locals want to ensure the traditional Bardstown experience doesn't disappear amid novel entertainment options.
Includes index.
Keywords: Tourism -- Economic aspects -- Kentucky.; Whiskey industry -- Economic aspects -- Kentucky.; Bourbon whiskey -- Kentucky.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Tourism industry.; elektronické knihy; electronic books